Association between dental consultation and oral health status among male Japanese employees - Shimazaki, Yoshihiro (J Occup Health, 2019)
OBJECTIVE: To investigate the association between dental consultation and oral health status among male Japanese employees. METHODS: The participants were 3351 male employees who received a workplace oral health examination conducted at the ages of 35, 40, 45, 50, 55, and 59 years before retirement in conjunction with an annual health checkup. Data on dental expenditures were collected from health insurance claims. The number of dental visits and dental care expenses, alone or in combination, were used as indices of the dental consultation status for the analyses. The effects of dental consultation status on oral health status (number of total teeth, number of decayed teeth, and periodontal status) were analyzed using multivariate multinomial logistic regression analyses adjusted for confounders. RESULTS: Multivariate analyses revealed that the odds ratio (OR) for 20‐27 teeth (losing 1‐8 teeth) was significantly higher (OR 1.4, 95% confidence interval (CI) 1.1‐1.7) in those who had a high number of dental visits and high dental care expenses than in those who did not have a dental visit. By contrast, the ORs for ≤19 teeth (losing ≥9 teeth), having ≥3 decayed teeth, or having a periodontal pocket ≥6 mm were significantly lower (OR 0.2, 95% CI 0.1‐0.6; OR 0.5, 95% CI 0.3‐0.6; OR 0.7, 95% CI 0.5‐1.0, respectively) in those who had fewer dental visits and lower dental care expenses. CONCLUSIONS: These results imply that the dental consultation status is associated with oral health status among male employees.